Keuntungan Usahatani Kunyit (Curcuma domestica Val) Di Desa Maniapun Pengaron Kabupaten Banjar - Fenny Refiana; Triatmoko, Eddy; Fitriadi, Subhan (Chlorophyl, 2023)
The purpose of this research is to know the revenue,the Total cost ,income and Profit. This research was conducted in Oktober– Desember 2023 at village Maniapun , Banjar regency. The sensus sampling methode used was by observing 9 farmers in village Maniapun who planted Turmeric plant.The Average land area 0,12/farmer,and Average result of the revenue is Rp. 3.013.888,89,/farmer, or Rp.25.115.740,75/Ha. The average Total cost is Rp. 1.216.035,29/farmer, and Average income profit Rp. 1.800.297,15/farmer, and From this result of development of farming Turmeric flant.We believe that it has good prospect and revenue, of the average profit income ,tecnicall,economically and increase in land area